The impacts of school autonomy on school organization: a grounded theory study in a public secondary school in Vietnam - Nguyen, Cuc Dieu; Justus Liebig University Giessen (My University, 2019)
This qualitative grounded study aimed to generate a substantive theory of the impacts of school autonomy on a school in Vietnam. It concerned with how teachers and school leaders perceive the impacts of school autonomy on four aspects of a school, namely educational processes, school structure, teachers, and school culture. School autonomy was defined as authority and responsibility which provides the freedom of schools to make decisions within a determined framework of goals, policies, standards and accountabilities. It is presented in three domains of education, organization and personnel, and financial resource management. Data collection was conducted in a selected public self-financed school in Vietnam. The study employed observations of school activities and semi-structured interviews with teachers and school leaders as methods of collecting data, and the grounded theory approach of Corbin & Strauss (1990) as the method of data analysis.The analysis of data revealed four themes: (a) school-based curriculum, (b) performance-based pay, (c) teachers, (d) school values. Research findings presented that school autonomy might be beneficiary to many aspects of a school. It increased school responsiveness to students needs and improved teaching and learning practice at the classroom level. Regarding school structure, teachers enjoyed an extensive autonomy over professional matters which was much higher than their peers in other regular public schools. The school strongly decentralized freedom to teacher groups to make professional decisions. The autonomy and responsibility of lead teachers were also significantly enlarged. For teachers, changes resulting from school autonomy contributed to an increase in teachers work motivation and job satisfaction. Key factors contributing to teacher job satisfaction were good pay, job security, recognition, meaningful work, and teacher collegiality. In terms of school culture, school autonomy shaped some positive values towards students such as respecting student autonomy, putting students benefits as the first priority, making every effort for students success, and supporting low-performance students. School autonomy was also a favorable factor in promoting organizational learning and developing the school as a learning community. The school tended to encourage teacher diversity within a school community and emphasized the need of establishing school distinctive values to differentiate it from other public schools. It is worth noting that school autonomy could only bring these benefits when it was accompanied by the necessary supporting conditions such as the quality of teaching staff and school leader, a sufficient school budget, school cultural values, and the supports of students parents.However, school autonomy was harmful where it could exacerbate teaching and learning to the test in the context of a test-oriented education in Vietnam. School autonomy context was recognized as a main factor heightening tensions between the school and local governing bodies. School autonomy significantly increased the school principal s autonomy whereas school council, teachers, and parents contributed only a weak voice in most school-level decisions. With greater professional authority from decentralization, lead teachers might misuse their authority or treat teacher members unfairly. Further, when working in the context of school autonomy, the workload and work-related stress of teachers were markedly increased. Four sources of work-related stress of teachers were teachers professional autonomy, school s requirements, administrative tasks, and maintaining harmonious relationships with students parents. When enjoying higher autonomy, schools would be less competitive than other public schools because students had to pay higher tuition fees instead of being covered by state subsidy. Finally, the distinctive school features resulting from school autonomy were big obstacles for the school to find suitable school partners and maintain collaborative relationships. Overall, this study contributed to the existing knowledge through the generation of a substantive theory of school autonomy and the formulation of recommendations for policy and school management practice.
Keywords: school autonomy; grounded theory methodology; education in Vietnam; qualitative research; ddc:370